Объяснение:
1) (x-4)(x+4)=0
x-4=0 x+4=0
x=4 x=-4
2) x+2=0 3x-8=0
x=-2 x=8/3
3) одз: х не равен 0
все уравнение умножаем на х
2x^2-3-5x=0
2x^2-5x-3=0
D: b^2-4ac: 25-4*2*(-3)=25+24=49
x1=(-b+)/2a=(5+7)/4=3
x2=(-b-)/2a=(5-7)/4=-1/2
4) x(x-2)=0
x=0 x-2=0
x=2
Объяснение:
1) (x-4)(x+4)=0
x-4=0 x+4=0
x=4 x=-4
2) x+2=0 3x-8=0
x=-2 x=8/3
3) одз: х не равен 0
все уравнение умножаем на х
2x^2-3-5x=0
2x^2-5x-3=0
D: b^2-4ac: 25-4*2*(-3)=25+24=49
x1=(-b+
)/2a=(5+7)/4=3
x2=(-b-
)/2a=(5-7)/4=-1/2
4) x(x-2)=0
x=0 x-2=0
x=2